2018
DOI: 10.3390/en11113147
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Inhibition of Aluminum–Methane–Air Flames by Fine NaCl Particles

Abstract: The effect of NaCl as an extinguishing agent on metal dust fires require further exploration. This paper reports the results of an experimental study on the performance of micron-sized NaCl powders on hybrid aluminum–methane–air flames. NaCl particles with sub-10 μm sizes were newly fabricated via a simple solution/anti-solvent method. The combustion characteristics of aluminum combustion in a methane-air flame were investigated prior to the particle inhibition study to verify the critical aluminum concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The nanoparticles fuel mixture affects the speed of the laminar flame. The combustion of aluminum particles methane-air mixture causes the release of additional heat, which will most likely increase the rate of combustion [24]. The laminar flame speed of butane-air has increased by 18.9% and 29.1% in terms of the addition of aluminum nanoparticles by 2 wt% and 5 wt%, respectively [25].…”
mentioning
confidence: 99%
“…The nanoparticles fuel mixture affects the speed of the laminar flame. The combustion of aluminum particles methane-air mixture causes the release of additional heat, which will most likely increase the rate of combustion [24]. The laminar flame speed of butane-air has increased by 18.9% and 29.1% in terms of the addition of aluminum nanoparticles by 2 wt% and 5 wt%, respectively [25].…”
mentioning
confidence: 99%
“…Many studies analyzed the effects of inert additives like CO2, H2O, He, and Ar on combustible mixtures' burning velocities. Xu and Jiang [79] studied the effects of adding NaCl to aluminum-methane-air flames over a range of dust concentrations, the LBV, and measured the established by using a modified nozzle burner. As a result, the burning velocity was reduced.…”
Section: Inert Additives Fuelmentioning
confidence: 99%
“…Zhao et al [15] studied the inhibitory effect of (NH4) 2 HPO 4 on the explosion of wheat dust and found that as the concentration of diammonium hydrogen phosphate increased, the ionic current in the explosion reaction zone of wheat dust first increased and then decreased, which could consequently inhibit the explosion of wheat dust. Xu and Jiang [16] compared the inhibitory effects of NaCl, SiO 2 and SiC on aluminum-methane-air flames, and NaCl had the best inhibitory effect, significantly slowing down the flame propagation. Lin et al [17] found experimentally that Al(OH) 3 could inhibit polyethylene dust explosion, and when the mass fraction of Al(OH) 3 powder reached above 80 wt%, it could inhibit polyethylene flame propagation.…”
Section: Introductionmentioning
confidence: 99%